Disabled young people's hopes and dreams in a rapidly changing society: a co-production peer research study. Issue 4 (1st April 2021) - Curran, Tillie; Jones, Matthew; Ferguson, Sarah; Reed, Mary; Lawrence, Abbie; Cull, Nikki; Stabb, Matt
Abstract: The idea that disabled young people should be at the centre of decision making about their future is promoted in policy, practice and research, yet this often translates into a narrow agenda on transitions through service and benefits systems. In this project, we aimed for an expansive exploration of disabled young people's hopes and dreams in the context of unprecedented societal changes. Co-production methods brought academics, members of a Centre for Independent Living, and nine peer researchers together to host knowledge cafes with fifty seven disabled young people. Peer researchers visited a robotic laboratory and developed key messages around the freedom to define their future that engaged stakeholders in the impact events they took part in. The themes: being responsible, giving love, freedom and happiness and a strong sense of self and togetherness, convey a more filled-out vision of disabled young people's futures and a new politics of the possible. Points of interest: A co-production research approach was chosen to explore and promote disabled young people's own views of their future in a rapidly changing society. Key themes arising from the research on 'being responsible', 'giving love', 'freedom and happiness' and a 'strong sense of self and togetherness', suggest rich visions of the future possibilities. New technologies, such as the automation in home and travel environments, were not highlighted by peer researchers, but were seen as possibilities supporting their key messages about quality of life. Peer researchers' presentation of their key messages to public sector workers and politicians focussed on independence and social connections, rather than welfare services and benefits. The project themes discussed here resonate with those of disabled young people involved in citizenship research internationally. Reflections question ideas about 'the future' for a wider rich vision of life.